PopArt : evoluzione di una generazione - Codognato, Attilio; Barthes, Roland; Bonito Oliva, Achille; Bourdon, David; Celant, Germano; Shapiro, David (Milano : Electa editrice, 1980)
Dine, Jim ; Lichtenstein, Roy ; Oldenburg, Claes ; Rosenquist, James ; Segal, George ; Warhol, Andy ; Wesselmann, Tom
Italiaans
boek